The characteristic differences of the four gospels considered as revealing various relations of the Lord Jesus Christ - Jukes, Andrew (Glasgow, Scotland Pickering and Inglis)
Inlcudes index.
Donated by the family of the lated Mr R. Scanlon.
Keywords: Bible. N.T. Gospels -- criticism, interpretation, etc